Tanah Wakaf Sebagai Jaminan Hutang Perspektif Hukum Islam dan Undang-Undang No 41 Tahun 2004 Tentang Wakaf (Studi Kasus Desa Tandem Hilir Kecamatan Hamparan Perak Kab. Deli Serdang) - Rina Siswi Utami; Zainal Arifin Purba (UNES Law Review, 2023)
The purpose of this study is to find out waqf land as debt security in Tandem Hilir Village, Hamparan Perak District, Deli Serdang Regency and also to find out waqf land as debt security according to Islamic law and Law No. 41 of 2004. This study used a descriptive method of analysis. This type of research is empirical research, the research used in this research is qualitative method. The collection technique in this study used interviews, observation, and documentation. The problem with the waqf land used as collateral for the debt occurred because of the ignorance of the waqf where his brother made the waqf land as collateral for debt, so that the waqf land could not be used as the initial designation of the waqf land for the expansion of the mosque area, until now the problem has not been resolved because the waqf's brother has not settled the debt, so the waqf land is still a collateral for the debt. Basically, changes in designation are not allowed, because it has been regulated by Law Number 41 of 2004 concerning Waqf article 40 that waqf assets are prohibited for collateral, confiscated, granted, sold, bequeathed, exchanged, transferred in other forms of transfer of rights. The criminal provisions regarding waqf land as debt security are regulated in Law No. 41 of 2004 Article 67. With the existence of criminal provisions and sanctions for perpetrators who violate the rules of Law No. 41 of 2004 concerning Waqf article 40, making it a person who commits the violation deterred with legal consequences and makes the community reluctant to violate.